2020
DOI: 10.1002/htj.21866
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of various fin geometries on the thermal performance of a heat sink under natural convection

Abstract: Experimentally investigates heat dissipation by different longitudinal fins fitted to a cylindrical heat sink under natural convection conditions. Five aluminum fin configurations at base temperatures (70°C, 85°C, 100°C, and 115°C) were studied. The first fin was plain (fin1), while second fin had a triangular edge (fin2). The rest fins have the same triangular edge but with six 1cm circular perforations near the edge (fin3). While the perforations in fin4 were in the middle longitudinal fin length. The last f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In an experimental study on a straight fin with a knurled surface, Chikurde et al 25 concluded that the increasing depth and height of knurled surface negates the recirculation of natural convection currents, which results in enhanced heat dissipation. The experimental analysis done by Hameed et al 26 revealed that the efficiency of the radial heat sink with triangular‐edged fins, under buoyancy‐driven flow, is more than that of a plain fin heat sink, which was further increased by providing holes nearer to the base of the fin. Sarwe and Kulkarni 27 came out with an analytical solution, DTM, for solving a nonlinear ordinary differential equation governing the heat transfer from an annular fin and found a decent agreement with the conventional numerical methods to solve the same.…”
Section: Introductionmentioning
confidence: 99%
“…In an experimental study on a straight fin with a knurled surface, Chikurde et al 25 concluded that the increasing depth and height of knurled surface negates the recirculation of natural convection currents, which results in enhanced heat dissipation. The experimental analysis done by Hameed et al 26 revealed that the efficiency of the radial heat sink with triangular‐edged fins, under buoyancy‐driven flow, is more than that of a plain fin heat sink, which was further increased by providing holes nearer to the base of the fin. Sarwe and Kulkarni 27 came out with an analytical solution, DTM, for solving a nonlinear ordinary differential equation governing the heat transfer from an annular fin and found a decent agreement with the conventional numerical methods to solve the same.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most straightforward and efficient methods to improve the heat transfer quality is using the fins, so it is not surprising that many numerical or experimental types of research forms have been conducted in that area 1–6 . In general, fins exchange heat with their surroundings in the form of convection, radiation, conduction, or a combination of these methods.…”
Section: Introductionmentioning
confidence: 99%